Amauroderma rugosum Protects PC12 Cells against 6-OHDA-Induced Neurotoxicity through Antioxidant and Antiapoptotic Effects. (10th February 2021) - Li, Jingjing; Li, Renkai; Wu, Xiaoping; Hoo, Ruby Lai-Chong; Lee, Simon Ming-Yuen; Cheung, Timothy Man-Yau; Ho, Bryan Siu-Yin; Leung, George Pak-Heng
Abstract : Amauroderma rugosum (AR) is a dietary mushroom in the Ganodermataceae family whose pharmacological activity and medicinal value have rarely been reported. In this study, the antioxidant capacity and neuroprotective effects of AR were investigated. The aqueous extract of AR was confirmed to contain phenolic compounds, polysaccharides, and triterpenes. The results of 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and total antioxidant capacity assays revealed that AR extract scavenged reactive oxygen species. Moreover, AR extract decreased the cytotoxicity, oxidative stress, mitochondrial dysfunction, and apoptosis of PC12 cells induced by 6-hydroxydopamine (6-OHDA). In addition, 6-OHDA upregulated the expressions of proapoptotic proteins and downregulated the Akt (protein kinase B)/mTOR- (mammalian target of rapamycin-) and MEK (mitogen-activated protein kinase kinase)/ERK- (extracellular signal-regulated kinases-) dependent signaling pathways. These effects of 6-OHDA were abolished or partially reversed by AR extract. Furthermore, the neuroprotective effects of AR in 6-OHDA-treated PC12 cells were significantly abolished by Akt and MEK inhibitor. Thus, AR extract possesses neuroprotective effects, probably through its antioxidant and antiapoptotic effects. These findings suggest the potential application of AR in the prevention or treatment of oxidative stress-related neurodegenerative diseases such as Parkinson's disease.